Church leaders as agents of peace: Transforming political violence through the gospel - Ndlovu, James; Masondo, Sibusiso (Verbum et ecclesia, 2025)
This article examines the multifaceted role of church leaders in mitigating political violence in Zimbabwe. The study draws on empirical qualitative interviews with church leaders to explore how they harness their social and religious connections, political engagement, religious authority and mediation skills to achieve successful mitigation and prevention of violent conflict. The study reveals that the roles of church leaders in mitigating political violence are multifaceted. The article discusses these roles in four underlying themes: (1) preventing violence by identifying potential political violence at grassroots level, (2) political involvement and the engagement dilemma, (3) spiritual and moral leadership role, and (4) mediation and dialogue, emphasising the role of ecumenical statements and pastoral letters as tools for fostering national conversations on peacebuilding. The findings highlight that the church, rather than a passive observer, is an active agent of change in the face of the pervading political violence. However, the study also brings to the fore the inherent challenges faced by the church leaders in exercising their roles in dealing with violent conflict, such as the risk of partisanship and the complexities in translating spiritual capital into measurable political outcomes. Intradisciplinary and/or interdisciplinary implications: This interdisciplinary study is located at the intersection of peace studies and political theology. It not only contributes to theoretical debates on conflict transformation in religious contexts but also offers practical insights for enhancing the peacebuilding role of the church in Zimbabwe and similar political contexts.